Utilização de fibras de vidro e eucalipto como reforço em telhas de concreto produzidas com vermiculita - Viana, Queilla Santos (2019)
This research aimed at evaluating the influence of using glass and eucalyptus fibers in the manufacture of concrete tiles produced with vermiculite. The substitution of 0%, 12.5%, 25%, 37.5% and 50% of the sand by vermiculite was evaluated, as well as the incorporation of 0.2% of glass fibers, 0.2% of eucalyptus fibers and 0.1% of both fibers. The concrete tiles were molded by the mechanical process, where simultaneous pressing and extrusion occurred. The control trace was composed of 21.95% CPV-ARI cement, 65.85% sand and 12.20% limestone. The tiles went through 28 days of healing after production and, posteriorly, the physical (tile classification, dry weight of samples, water absorption and porosity), mechanical (resistance of the breaking load to bending) and microstructure properties were evaluated. All treatments were assessed before and after accelerated aging. The thermal properties and the economic-financial viability of the modification in the structure of concrete tiles were also analyzed. Through the results, regarding the use of vermiculite, one can conclude that: A) There was a significant effect on the physical and mechanical properties as the substitution of the sand by the vermiculite occurs. Only the control treatment and the 12.5% substitution treatment are in line with all specifications of norm NBR 13858-2 (2009), at 28 days of healing. B) The tiles produced with vermiculite demonstrated a need for longer healing time so that the raw material can be used in greater proportions. C) The use of vermiculite reduced the thermal conductivity of the tiles. D) The higher the percentage of vermiculite, the greater the cost applied in production increases, the replacement of sand by vermiculite provided a rise of the cost with raw materials in 19.23; 38.46; 57.69 and 76.92%. Regarding the addition of the fibers, can be concluded that: A) The fibers promoted significant variation of the physical and mechanical properties, in which only the control treatment is in line with all specifications of norm NBR 13858 -2 (2009), at 28 days of healing and after the accelerated aging. B) The addition of the fibers did not provide significant variation in the thermal conductivity of the tiles. C) The cost with raw materials suffered an increase with the inclusion of eucalyptus fibers by 0.21%, of glass fibers by 56.68% and of both fibers by 28.44%.